2016
DOI: 10.1002/cplu.201600202
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Induced Cell‐Sheet Harvest on TiO2 Films Sensitized with Carbon Quantum Dots

Abstract: Carbon quantum dots (CQDs) have been incorporated as a sensitizer into TiO2 films to regulate the light‐induced cell‐detachment performance. Depending on the amount of CQDs incorporated, nanodots or porous films are obtained. It was found that the right amount of CQDs incorporation significantly improves the cell‐sheet detachment efficiency, and an intact cell sheet could be obtained after merely five minutes of UV illumination (365 nm, UV365), which is much faster than that from CQDs‐free TiO2 film. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“… 25 , 59 These changes could lead to the conformational changes in or the release of the adhesive proteins or collagens, which contributed to cell detachment. In addition, electron–hole (e − /h + ) pairs occur on the TiO 2 surfaces under UV illumination, 60 and then the potential change induced by electron accumulation would also manipulate protein release. 61 When adopting light illumination for cell harvesting, the wavelength and light dose (depending on power density and irradiation time) must be defined first.…”
Section: Discussionmentioning
confidence: 99%
“… 25 , 59 These changes could lead to the conformational changes in or the release of the adhesive proteins or collagens, which contributed to cell detachment. In addition, electron–hole (e − /h + ) pairs occur on the TiO 2 surfaces under UV illumination, 60 and then the potential change induced by electron accumulation would also manipulate protein release. 61 When adopting light illumination for cell harvesting, the wavelength and light dose (depending on power density and irradiation time) must be defined first.…”
Section: Discussionmentioning
confidence: 99%
“…However, UV exposure may cause potential damage to cells during the separation, so it is important to minimize the light dose. Wang et al incorporated the carbon quantum dots as a sensitizer into TiO 2 films and managed to shorten the exposure time from 20 min to 5 min for cell detachment [172]. The carbon quantum dots sensitization helped increase negative charge and caused changes in the secondary structure of adsorbed protein molecules.…”
Section: Light-based Cell Sheet Generationmentioning
confidence: 99%
“…In some studies, carbon quantum dots (CQDs) were added to TiO 2 films, resulting in faster CS detachment in response to UV (365 nm) irradiation than CQD-free films. 60 Other elements incorporated into these TiO 2 films include SiO 2 , Zn, and Gr, resulting in the spontaneous and rapid detachment of functionally intact cell sheets. [60][61][62] Moreover, TiO 2 film surfaces decorated using organic materials have been utilized, as in the case of two studies demonstrating that TiO 2 films with surface-immobilized RGD peptides can improve the adhesion of cells while allowing for rapid cell sheet detachment within 30 min upon UV (365 nm) irradiation.…”
Section: Photo-responsive Systemsmentioning
confidence: 99%
“…60 Other elements incorporated into these TiO 2 films include SiO 2 , Zn, and Gr, resulting in the spontaneous and rapid detachment of functionally intact cell sheets. [60][61][62] Moreover, TiO 2 film surfaces decorated using organic materials have been utilized, as in the case of two studies demonstrating that TiO 2 films with surface-immobilized RGD peptides can improve the adhesion of cells while allowing for rapid cell sheet detachment within 30 min upon UV (365 nm) irradiation. 63,64 A 2017 study explored the use of recombinant human laminin-521 to modify TiO 2 films and found that an intact cell sheet characterized by improved proliferation and adhesion could be attained using this strategy.…”
Section: Photo-responsive Systemsmentioning
confidence: 99%
See 1 more Smart Citation